Role of magnetic resonance imaging in evaluation of patients with chronic primary headaches - Sanju Rawal; Subhash Chandra Yadav; Bardan Oli; Rajendra KC; Krishna Thapa; Sadhan Mukhi; Ranjit Kumar Jha (Journal of Universal College of Medical Sciences, 2026)
INTRODUCTION Headaches are often associated with neurological disorders and contribute to the growing global health challenges. They can be classified as primary or secondary. Magnetic Resonance Imaging (MRI) has become increasingly crucial for understanding the underlying mechanisms of chronic primary headaches. This study aimed to evaluate the significance of MRI in the assessment of patients with chronic primary headache. MATERIAL AND METHODS This cross-sectional study was conducted on 140 patients who underwent brain MRI from March to September 2025 at the Department of Radiodiagnosis and Medical Imaging, Universal College of Medical Sciences and Teaching Hospital, Nepal. Siemens Magnetom Lumina 3T MRI was utilized for all scans. Data analysis was performed using SPSS version 20. RESULTS Of the 140 patients, 57.14% were female and 42.86% were male. The mean age was 45.19 years (SD±14.86), and ages ranged from 12 to 77 years. The largest proportion of patients was in the 31-40 age group, representing about 24.28% of the total participants. Migraine was the most common type of headache observed, comprising 65% of cases. CONCLUSION This study evaluated MRI findings in patients with chronic primary headaches who were referred for imaging. The majority of participants were female, and the MRI results appeared mostly normal.